2004
DOI: 10.1002/ptr.1492
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase inhibitory flavonoids from the stem bark of Semecarpus anacardium Linn.

Abstract: The ethyl acetate extract of stem bark of Semecarpus anacardium showing in vivo anti-in fl ammatory activity in carrageenan induced rat paw edema assay was investigated in order to identify its active compounds. Chemical investigation of the ethyl acetate extract of S.anacardium afforded 3,4,2',4'-tetrahydroxychalcone (butein) and 7,3',4'-trihydroxy fl avone. Evaluation of COX-1 inhibitory activity of 3,4,2',4'-tetrahydroxychalcone and 7,3',4'-trihydroxy fl avone provided the IC(50) values of 28.4 and 36.7 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…On the other hand, none of the tested compounds was able to inhibit COX-2. Still, it is conceivable that this kind of effect might be seen at higher concentrations in accordance to what has been previously observed with a structural-similar compound (7,3 0 ,4 0 -trihydroxyflavone) [37]. However, due to solubility issues, the studied 2-SC could not be tested at higher concentrations.…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, none of the tested compounds was able to inhibit COX-2. Still, it is conceivable that this kind of effect might be seen at higher concentrations in accordance to what has been previously observed with a structural-similar compound (7,3 0 ,4 0 -trihydroxyflavone) [37]. However, due to solubility issues, the studied 2-SC could not be tested at higher concentrations.…”
Section: Discussionsupporting
confidence: 72%
“…Briefly, the cells (5 Â 10 3 /mL) were incubated in triplicate in a 96-well plate in the presence or absence of indicated concentration of butein in a final volume of 0.2 mL for different time intervals at 37 C. Thereafter, 20 mL MTT solution (5 mg/mL in PBS) was added to each well. After a 2-hour incubation at 37 C, 0.1 mL lysis buffer (20% SDS, 50% dimethylformamide) was added, incubation was continued overnight at 37 C, and then the optical density at 570 nm was measured by Tecan plate reader.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Previous reports have indicated that butein can suppress the proliferation of different human tumor cells, including breast carcinoma, colon carcinoma, osteosarcoma, lymphoma, acute myelogenous leukemia, chronic myeloid leukemia, multiple myeloma, melanoma, and hepatic stellate cells (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Furthermore, it was found to suppress phorbol ester-induced skin tumor formation (36), inhibit carrageenan-induced rat paw edema (37), reduce antibodyassociated glomerulonephritis (38), and suppress liver fibrosis induced by carbon tetrachloride (32). Moreover, butein was recently reported to induce G 2 /M phase arrest and apoptosis in HCC cells through reactive oxygen species (ROS) generation and activation of (JNK; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Varieties of phytochemicals flavonoids, terpenoids, alkaloids and saponins are possess anti-inflammatory property 20 . Flavonoids inhibits biosynthesis of prostaglandins which is the end product of COX and lipoxygenase pathways, which acts as a secondary messengers and are involved in various immunologic responses 21 -23 .…”
Section: Fig 5: Graphical Representation Of Antiinflammatory Activitmentioning
confidence: 99%